ANALYSIS OF MACRO ECONOMIC FACTORS THAT INFLUENCE MUTUAL FUND PERFORMANCE SHARIA IN INDONESIA (2015-2019 PERIOD) - Srie Nuning Mulatsih; Aisyah Ratnasari (International Conference on Social and Islamic Studies, 2021)
This study is to analyze the effect of macroeconomic factors namely inflation, the amount of money circulating, and exchange rate of the sharia mutual funds in the measure through the value net assets of sharia mutual fund. This study uses quantitative approach with purposive sampling determination technique, the data used in this research is data time series or monthly data since January 2015 until December 2019. This research uses multiple linear analysis method. The results of this study indicate that there is a positive and significant effect between inflation, the money supply (M2) and the exchange rate (exchange rate) on the Net Asset Value (NAV) of Islamic mutual funds of 84.2%. As for 15.8% performance Islamic mutual funds are influenced by other variables or factors that are not included in this study.